Strategy to reduce the acclimation period for enrichment of PHA accumulating cultures. Issue 60 (25th December 2016) - Guo, Zirui; Chen, Zhiqiang; Wen, Qinxue; Huang, Long; Bakke, Rune; Du, Maoan
Abstract: A selective sludge discharge (SSD) process is proposed and evaluated in this study to accumulate the polyhydroxyalkanoate (PHA) accumulating bacteria in mixed microbial cultures (MMCs). Sequencing batch reactor (SBR) PHA production in the SSD mode was compared to the conventional aerobic dynamic feeding (ADF) mode. Aerobic granular sludge rich in PHA was cultivated in a SBR by seeding the MMCs. The granular sludge was formed on 14 and 8 d of the operation in SBR #1 and SBR #2, respectively, however, the PHA production performance of SBR #1 fluctuated during the 30 d. The MMCs in SBR #2 showed the best PHA accumulating ability in terms of the yield of PHA, specific substrate uptake rate and PHA storage rate, a maximum PHA content and average PHA storage rate of 58.2% and 0.33 Cmol PHA/(Cmol X/h), respectively, were achieved on the day 30 of enrichment operation in the batch assays.